PENGARUH KARAKTERISTIK INDIVIDU, DISIPLIN KERJA, DAN MOTIVASI TERHADAP KINERJA KARYAWAN WANITA PADA GUDANG TEMBAKAU UD. SINAR MADURA JAYA - Solehah, Nur Ilmiatus; Supeni, Retno Endah; Izzudin, Ahmad (Relawan Jurnal Indonesia, 2023)
Individual characteristics, work discipline and motivation are factors that can influence employee performance. The research aims to examine and analyze the significant influence of individual characteristics, work discipline, and motivation on employee performance at the UD. Sinar Madura Jaya. The type of research used is quantitative research with data collection techniques using observation, questionnaires, documentation and interviews with 60 respondents using census techniques. The analytical tools used in this study are validity test, reliability test, classic assumption test, multiple linear regression analysis, T test, and R2 test. The results of testing the first hypothesis (H1) show that the individual characteristic variable is 0.197 which is greater than 0.05 which means that the individual characteristic variable has no effect on employee performance. The results of testing the second hypothesis (H2) show that the work discipline variable is 0.096 where the value is greater than 0.05, so it can be concluded that the work discipline variable has no influence on employee performance. The results of testing the third hypothesis (H3) show that the motivation variable is 0.000 where the value is smaller than 0.05, so it can be concluded that the motivational variable has an influence on employee performance.